A pilot study on health risk assessment based on body loadings of PCBs of lactating mothers at Taizhou, China, the world's major site for recycling transformers - Man, Yu Bon; Chow, Ka Lai; Xing, Guan Hua; Chan, Janet Kit Yan; Wu, Sheng Chun; Wong, Ming Hung (Environmental pollution (1987), 2017)
Our early study reported an extraordinarily high Estimated Daily Intake (EDI) of PCBs of lactating mothers from Taizhou, Zhejiang Province, China (based on a food consumption survey and food basket analysis). The EDI well exceeded the intake limit stipulated by FAO/WHO 70 pg TEQ/kg body weight (bw)/month. The present pilot study provided further information on PCBs body burden in lactating mothers of Taizhou. The total PCBs detected in human milk, placenta and hair samples of these lactating mothers were 363 ng/g lipid, 224 ng/g lipid, and 386 ng/g dry wt. Respectively, three times higher than those samples collected from the reference site (Lin'an). Compared with the previous reported values in the 3rd WHO coordinated study, Taizhou topped the list of 32 countries/regions with regards to WHO-PCB-TEQ values of milk samples, which could be attributed to the relatively higher level of PCB-126 derived from electronic waste. In addition, the corresponding EDI of PCBs of Taizhou mothers (12.9 pg WHO-PCB-TEQ/kg bw/day) and infants (438 pg WHO-PCB-TEQ/kg) were derived from individual congener levels in human milk. The results were also higher than the tolerable daily intakes recommended by WHO (1–4 pg WHO-TEQ/kg bw/day) by 3 and 110 times, for mothers and infants, respectively. A more intensive epidemiological study on the potential health effects of e-waste recycling activities affecting both workers and residents seems to be of top priority, based on findings of this pilot study. •Highest TEQ detected in human milk (Taizhou) amongst other countries or cities.•Highest PCB detected in placenta/hair samples (Taizhou & Li'an) amongst worldwide.•E-waste workers/residents in Taizhou had high levels of PCBs in body tissues. The present results showed that human exposure to high levels of PCBs in this intensive e-waste processing site is of high public health concern, especially workers and residents living in the vicinity.